Upaya Dalam Mengurangi Limbah Sampah Plastik Melalui Aplikasi Amara Recycle (Current Research in Education: Conference Series Journal, 2022)
Plastic waste management in Indonesia is still a problem that cannot be resolved properly. Data from the Olefins, Aromatic and Plastics Industry Association (INAPLAS) and the Central Statistics Agency (BPS) show that plastic waste in Indonesia has reached 64 million tons per year. And as many as 3.2 million tons of which are plastic waste dumped into the sea, as well as 10 billion plastic bags disposed of into the environment per year or as many as 85,000 tons of plastic bags. The Ministry of Environment and Forestry targets to reduce plastic waste by more than 1.9 million tons by 2019. Handling plastic waste has also been widely implemented with the 3R concept (Reuse, Reduce, Recycle). With this phenomenon, we as Information Systems developers design an application that can be used in good, appropriate and environmentally friendly plastic waste management in the community. The application we offer is